2021
DOI: 10.1093/nar/gkab162
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-mediated translation repression through GYF-1 and IFE-4 in C. elegans development

Abstract: microRNA (miRNA)-mediated gene silencing is enacted through the recruitment of effector proteins that direct translational repression or degradation of mRNA targets, but the relative importance of their activities for animal development remains unknown. Our concerted proteomic surveys identified the uncharacterized GYF-domain encoding protein GYF-1 and its direct interaction with IFE-4, the ortholog of the mammalian translation repressor 4EHP, as key miRNA effector proteins in Caenorhabditis elegans. Recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…To exert their regulatory roles, miRNAs are loaded into Argonaute (AGO) proteins to form a miRNA Induced Silencing Complex (miRISC), which ultimately associates with an effector protein GW182. miRISC binding to the target mRNA via partial sequence complementarity between a miRNA and 3′ UTR of mRNA triggers a series of gene silencing mechanisms including translation inhibition, decapping, and mRNA decay 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…To exert their regulatory roles, miRNAs are loaded into Argonaute (AGO) proteins to form a miRNA Induced Silencing Complex (miRISC), which ultimately associates with an effector protein GW182. miRISC binding to the target mRNA via partial sequence complementarity between a miRNA and 3′ UTR of mRNA triggers a series of gene silencing mechanisms including translation inhibition, decapping, and mRNA decay 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Reinhart et al found another important miRNA: let-7 posttranscriptional regulation: let-7 in wireworms. The discovery of lin-4 and let-7 kicked off the research on miRNA [ 5 , 6 ]. With the improvement of research methods and the increasing attention paid to miRNA, more and more miRNA molecules are constantly revealed in a variety of organisms and become biomarkers for the diagnosis of diseases and tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila , PatL1 associates with the Ddx6 (Me31B) and GIGYF proteins to repress translation ( Peter et al, 2019 ). The same interaction between PatL1 (PATR-1) and GIGYF (GYF-1) has also been reported in C. elegans , where GYF-1 represses translation of some developmental miRNA targets ( Mayya et al, 2021 ). Thus, promotion of decapping and decay or translational repression by PatL1 seems to depend on its specific interactions and on environmental and developmental contexts.…”
Section: Decapping Activatorsmentioning
confidence: 52%